Small bowel perforation caused by applicator implantation in high-dose-rate interstitial brachytherapy for recurrent pelvic tumor: a case report - Koji Masui; Hideya Yamazaki; Gen Suzuki; Daisuke Shimizu; Tadashi Takenaka; Yasuhiro Yamada; Koji Okihara; Yoshiaki Kuriu; Kei Yamada (Journal of Contemporary Brachytherapy, 2020)
High-dose-rate interstitial brachytherapy (HDR-ISBT) is widely used for the treatment of pelvic tumors. However, there are a few reports on complications of applicator implantation in HDR-ISBT. We describe a case of small bowel perforation caused by applicator implantation in an 82-year-old male patient with recurrence tumor in the pelvis treated with HDR-ISBT. Eventually, the patient underwent laparotomy and partial intestinal resection. We recognized the site where the applicator was inserted into a part of the tumor on the mucosal surface. Pathological examination confirmed that the tumor had infiltrated the small intestine directly and that the infiltrated part had reached the submucosa. This is the first published report about small bowel perforation caused by applicator implantation. In cases where intestinal infiltration of the tumor is suspected, HDR-ISBT should be performed with maximum caution.